Essential Role of Lyn in Fibrosis - Pham, Hung; Birtolo, Chiara; Chheda, Chintan; Yang, Wendy; Rodriguez, Maria D.; Liu, Sandy T.; Gugliotta, Gabriele; Lewis, Michael S.; Cirulli, Vincenzo; Pandol, Stephen J.; Ptasznik, Andrzej (Frontiers in Physiology, 2016)
Fibrotic disorders involve replacement of normal parenchyma with myofibroblasts, which deposit connective tissue, leading to obliteration of the function of the underlying organ. The treatment options are inadequate and reflect the fact that signaling targets in myofibroblasts are unknown. Here we identify the hyperactive Lyn signaling in myofibroblasts of patients with chronic pancreatitis-induced fibrosis. Lyn activation coexpress with markers of activated myofibroblasts, and is increased 11-fold in chronic pancreatitis compared to normal tissue. Inhibition of Lyn with siRNA or INNO-406 leads to the substantial decrease of migration and proliferation of human chronic pancreatitis myofibroblasts in vitro, while leaving migration and proliferation of normal myofibroblasts only slightly affected. Furthermore, inhibition of Lyn prevents synthesis of procollagen and collagen in myofibroblasts in a mouse model of chronic pancreatitis-induced fibrosis. We conclude that Lyn, as a positive regulator of myofibroblast migration, proliferation and collagen production, is a key target for preventing fibrosis.